2022
DOI: 10.37481/sjr.v5i2.473
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penerapan Sistem Informasi Manajemen (Sim), Komunikasi Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Dinas Sosial Kota Bima

Abstract: The purpose of this study was to analyze the influence of management information systems, communication and work motivation on the performance of employees of the Bima City Social Service. This research is a causal research (cause-effect), meaning that this research is a quantitative study to analyze the causal effect between Management Information Systems, Communication and Motivation on Employee Performance at the Bima City Social Service. The sample of this study were 71 civil servants and non-civil servant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
2
0
0
Order By: Relevance
“…This means that the better the implementation of SIMRS used in drug management, the better the employee performance will be. This is in accordance with research conducted by Siregar (2022), Dewi, et al, (2022), Lumbanraja (2017) and Larasati. et al, (2013) [9,[24][25][26] which revealed that the existence of a management information system will improve employee performance for the better, effective and efficient.…”
Section: Hypothesis Testsupporting
confidence: 93%
See 1 more Smart Citation
“…This means that the better the implementation of SIMRS used in drug management, the better the employee performance will be. This is in accordance with research conducted by Siregar (2022), Dewi, et al, (2022), Lumbanraja (2017) and Larasati. et al, (2013) [9,[24][25][26] which revealed that the existence of a management information system will improve employee performance for the better, effective and efficient.…”
Section: Hypothesis Testsupporting
confidence: 93%
“…This is in accordance with research conducted by Siregar (2022), Dewi, et al, (2022), Lumbanraja (2017) and Larasati. et al, (2013) [9,[24][25][26] which revealed that the existence of a management information system will improve employee performance for the better, effective and efficient. The implementation of SIMRS, which is used in carrying out drug management at the RSPAU Pharmaceutical Installation, dr. S. Hardjolukito, is expected to improve employee performance and provide benefits for hospitals which is characterized by the implementation of work programs effectively and efficiently in accordance with what has been planned.…”
Section: Hypothesis Testsupporting
confidence: 93%